A facile methodology using quantum dot multiplex labels for tracking co-transfection. Issue 35 (27th June 2019) - Kretzmann, Jessica A.; Feng, RuiLu; Munshi, Alaa M.; Ho, Diwei; Ranieri, Anna M.; Massi, Massimiliano; Saunders, Martin; Norret, Marck; Iyer, K. Swaminathan; Evans, Cameron W.
Abstract : The development of efficient non-viral transfection agents capable of delivering multiple nucleic acids is crucial for the field of genome engineering. Herein a facile methodology of polyplex labelling and tracking with quantum dots is presented. Abstract : Advances in the field of genome engineering demand the development of efficient non-viral transfection agents capable of delivering multiple distinct nucleic acids efficiently to cells (co-transfection). However, current delivery methods result in lower co-transfection efficiency than single plasmid transfections, and the efficiency decreases further with increasing numbers of plasmids. The development of a high-throughput methodology is required for the validation of co-transfection platforms to facilitate independent tracking of not only the multiple DNA plasmids during transfection but also the localisation of transfection agents. This is pivotal to determine the bottlenecks in achieving high transfection efficiencies at various stages of the cell internalisation and plasmid expression process. Herein we demonstrate that this can be achieved using a facile methodology in which quantum dots (QDs) are used to label two different plasmid DNA assemblies that are delivered to cells simultaneously using a dendronised polymer system. Multispectral confocal imaging can be used to separate signals from each polyplex as well as the expressed fluorescent reporter proteins to determine whether co-transfection difficulties result from poor internalisation or the inability of DNA to escape from polyplexes. The results demonstrate the utility of this facile approach to label polyplexes without interfering with gene expression, and enable high-throughput screening of transfection reagents for achieving optimal co-transfection.